Child beggars in Kosovo - Fetahu, Besnik (Ревија за социјална политика/Journal of Social Policy, 2017)
Ву using the method of interview, this paper does not represent the total ѕсоре of child beggars in Kosovo, but provides information based on 20 different саѕеѕ regarding this issues. The aim of this paper is to understand and to analyze the overall perception of the public opinion, conceming the relationship between child labor and education. It will try to identify and refiect on the types of common activities among children who work, their working conditions and the links between child labor and education. Тhе paper will note that some of these children are forced onto the streets by their parents. Also, we will not exclude the possibilities that lie behind these children's tutors, who are trying to use children, including elements of trafficking. These are the most important issues which will be elaborated in this paper.
Keywords: child beggar; trafficking; poverty; wellbeing; criminal groups; child protection